Implementasi Gerakan Keuangan Hijau Keluarga Melalui Optimasi Lahan Perumahan, Pengelolaan Limbah Terintegrasi, dan Konservasi Energi - Romi Kurniadi; Yoan Mareta; Kuswanto Kuswanto; Sahara Sahara; Ilham Falani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This programme focuses on the urgency of green finance education at the household level through a Participatory Action Research (PAR) approach. The programme focused on household waste management, limited land use for agriculture, and energy-saving engineering in Akana 4 Housing Estate, Pematang Gajah Village, Muaro Jambi Regency. The results of the programme showed an increase in housewives' participation in waste management activities, farming skills on limited land, and adoption of energy-saving technologies. The programme successfully encouraged behavioural changes, such as waste segregation and energy saving, which had a positive impact on household financial management as well as economic and environmental well-being.